Pengendalian Internal dan Transparansi terhadap Pencegahan Fraud: Studi Kasus pada Inspektorat Kabupaten Gorontalo - Yuliana Mangopa; Hartati Tuli; Ayu Rakhma Wuryandini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The study aims to identify the impact of the variables of Internal Control and Transparency on fraud prevention. (Studi Kasus Pada Inspektorat Kabupaten Gorontalo). The method used in research is a quantitative method with primary data obtained from questionnaire data that is measured using a likert scale. The sample collection process used a saturated sample with a total sample of 53 respondents. The data collected was then analyzed using a double linear regression test using the SPSS program version 26. The results of the research show that: 1) Internal controls have a significant impact on the Prevention of Fraud in the Gorontalo District Inspectorate. 2) Transparency has a significant influence on the prevention of fraud in Gorontalu District Inspection. 3) Fraud prevention in the gorontalo district inspectorate with a determination coefficient of 87.4% while the remaining 12.6% can be explained by other variables not studied in this study